Boolean algebra
Algebraic laws
Many of the laws that obtain in the mathematical realm of algebra also obtain for Boolean expressions.
The Commutative Law
$$ x \land y = y \land x \\ $$
$$
x \lor y = y \lor x
$$
Compare the Commutative Law in the context of arithmetic.
The Associative Law
$$ x \land (y \land z) = (x \land y) \land z $$
$$ x \lor (y \lor z) = (x \lor y) \lor z $$
Compare the Associative Law in the context of arithmetic.
The Distributive Law
$$ x \land (y \lor z) = (x \land y) \lor (x \land z) $$
$$ x \lor (y \land z) = (x \lor y) \land (x \lor z) $$
Compare how the Distributive Law applies in the case of algebra based on arithmetic:
$$ a \cdot (b + c) = a \cdot b + a \cdot c $$
Double Negation Elimination
$$ \lnot \lnot x = x $$
Idempotent Law
$$ x \land x = x $$
Combining a quantity with itself either by logical addition or logical multiplication will result in a logical sum or product that is the equivalent of the quantity
DeMorgan’s Laws
In addition we have DeMorgan’s Laws which express the relationship that obtains between the negations of conjunctive and disjunctive expressions:
$$ \lnot(x \land y) = \lnot x \lor \lnot y $$
$$ \lnot (x \lor y) = \lnot x \land \lnot y $$
Applying the laws to simplify complex Boolean expressions
Say we have the following expression:
$$ \lnot(\lnot(x) \land \lnot (x \lor y)) $$
We can employ DeMorgan’s Laws to convert the second conjunct to a different form:
$$ \lnot (x \lor y) = \lnot x \land \lnot y $$
So now we have:
$$ \lnot(\lnot(x) \land (\lnot x \land \lnot y )) $$
As we have now have an expression of the form P and (Q and R) we can apply the Distributive Law to simplify the brackets (P and Q and R):
$$ \lnot( \lnot(x) \land \lnot(x) \land \lnot(y)) $$
Notice that we are repeating ourselves in this reformulation. We have \(\lnot(x) \land \lnot(x)\) but this is just the same \(\lnot(x)\) by the principle of idempotence. So we can reduce to:
$$ \lnot(\lnot(x) \land \lnot(y)) $$
This gives our expression the form of the first DeMorgan Law (\(\lnot (P \land Q)\)), thus we can apply the law (\(\lnot P \lor \lnot Q\)) to get:
$$ \lnot(\lnot(x)) \lor \lnot(\lnot(y)) $$
Of course now we have two double negatives. We can apply the double negation law to get:
$$ x \lor y $$
Truth table
Whenever we simplify an algebraic expression the value of the resulting expression should match that of the complex expression. We can demonstrate this with a truth table:
\(x\) | \(y\) | \(\lnot(\lnot(x) \land \lnot (x \lor y))\) | \(x \lor y\) |
---|---|---|---|
0 | 0 | 0 | 0 |
0 | 1 | 1 | 1 |
1 | 0 | 1 | 1 |
1 | 1 | 1 | 1 |
Significance for computer architecture
The fact that we can take a complex Boolean function and reduce it to a simpler formulation has great significance for the development of computer architectures, specifically logic gates. It would be rather resource intensive and inefficient to create a gate that is representative of the complex function. Whereas the simplified version only requires a single OR gate.